Recognition through Numbers: Muslim Population Numbers and the Hui in Modern China - Li, Gang (Journal of the European Association for Chinese Studies, 2025)
Islam and Muslims have been in China for over a millennium; however, it was during the late nineteenth and early twentieth centuries that their demographic situation came under various kinds of scrutiny. Previous scholarship has focused on the reconstruction of “correct” statistics of the Muslim population in modern China. This paper, inspired by the sociology of quantification, aims at an investigation into the “making” and “doing” of Muslim population numbers in late-Qing and Republican China. It presents case studies regarding how the Muslim demographic numbers were produced, in which socio-political contexts they emerged, and what purposes and meanings they imply for those who produced them. The article will focus on the relations between the Muslim population numbers and the identity construction of the Hui Muslims in the context of China’s transition into a modern nation-state. Particular attention will be given to the production and circulation of the number of 50 million. 伊斯蘭教及穆斯林在中國的歷史淵源可追溯至千年以上，然而，直至19世紀末20世紀初，穆斯林人口狀況才開始受到各方關注並得以系統研究。既往研究多聚焦於重構中國近現代史中穆斯林人口的“正確”統計數據。本文則從計量社會學（sociology of quantification）的理論出發，探討清末與民國時期穆斯林人口數據的“建構”與“運作”機制。通過案例研究，本文分析穆斯林人口數據的生成過程、其背後的社會歷史背景，以及這些數據對其生產者的實際意義與功能。本研究特別關注穆斯林人口數據與回族穆斯林身份建構之間的關係，並將其置於中國傳統社會向現代民族國家轉型的宏觀歷史背景中加以考察。此外，本文著重討論了“五千萬”這一關鍵數字的形成及其社會傳播機制。